Separable or inseparable - relationship between companies' corporate social responsibility activities and financial performance: a Malaysian paradigm - Arulanandam, Benedict Valentine*; Ardelean, Ben-Oni; Maniam, Vikineswaran A (Technical University of Cluj-Napoca, 2022)
The study of corporate social responsibility CSR has been a very prominent one. This study examines the CSR activities of Malaysian firms and their respective financial performances. The purpose of this study is to examine the relationship between firms’ CSR activities and their financial performance. A total of 50 listed companies were selected based on market capitalization from the years 2015 – 2019. Financial and CSR information were obtained from the annual reports of firms. An in-depth content analysis approach was applied together with the method of a checklist to measure CSR, coupled with financial performance. The statistical software package (SPSS) was used to analyze the data collected. The results indicated no significant relationship between the CSR activities of the firm and their financial performance during the said period.